Scaphoid instability caused by a giant cell tumour of the tendon sheath: A case report. Issue 3 (March 2018) - Wang, Yanjun; Zhu, Xiaoxiao; Pei, Genwang; Zeng, Xianshang; Chen, Deng; Zuo, Yonggang; Yu, Weiguang; Ge, Zhe; Zhang, Xinchao
Giant-cell tumour of the tendon sheath (GCTTS) is a soft tissue tumour that may invade bone, causing an intrinsic osseous lesion or instability on radiographs. A case with scaphoid instability caused by a histologically-confirmed neighbouring GCTTS has rarely been described in the literature. No definite and radical method is available for the treatment of GCTTS. This report describes an unusual case of a 22-year-old woman who previously experienced a GCTTS in her right elbow, which was removed 10 years earlier. Currently, she presented with an enlarged painless right wrist mass with focal swelling. The mass has been present for 5 years. During the previous 6 months, she felt something pop and experienced pain with limited motion in her right wrist. Magnetic resonance imaging demonstrated a well-circumscribed soft tissue mass. Under general anaesthesia, complete surgical resection of the mass was undertaken. Histopathological examination revealed that the mass was a GCTTS. Less invasive leverage reduction with external fixator support and iliac crest bone autologous graft for treatment of carpal instability were performed. Radical resection combined with external fixator support and bone grafting can provide a new option for the treatment of carpal instability.